The Image of the Profession among the Specialists of the Special Working Conditions of Primorsky Region - Lyukshina D.S.; Kalita V.V. (Психолого-педагогические исследования, 2018)
The aim of the research is to describe the image of the profession that the experts of the Border, Police and Customs services have. Today, the future of the Russian Federation mostly depends on these experts’ rate of psychological readiness, level of professional skills and qualification, their ability to solve problems of high complexity. The technique of Serkin V.P. "Specialized semantic differential for the profession assessment" was used as the main technique. The research with participation of the employees of the Border (n = 100), Police (n = 100) and Customs services (n = 100) was carried out. The procedure of calculating of the semantic was selected for the processing of the results. Two common were revealed: the image of profession in three groups of experts working in special conditions is reconstructed, as “skilled” and “highly responsible”. At the Border service the image of profession is characterized by the following psychological characteristics: complex, active, tense, demanded, comprehended. At the Police service the image of profession is described as educational, perspective, common. At the Customs service the image of profession is characterized as complex, active, tense, demanded, sociable. The achieved results can be used in consulting work with the employees Border service of the FSB Russia for the Primorye territory, of the territorial bodies of the Police and the Customs services of the Primorsky Region, as well as by the heads of the services and their divisions for increasing the efficiency and professional work productivity.